ANALYSIS OF THE ADOPTION LEVEL OF INTEGRATED CROP MANAGEMENT FOR RICE COMMODITIES IN THE SESAYAP DISTRICT - Paolus Donatus Haka; Abdul Rahim; Nia Kurniasih Suryana1 (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
Over the last three years, Paddy rice production in Tana Tidung Regency has been approximately 500-700 tons. This production is considered low, even when compared to rice production in other regencies located in North Kalimantan Province. One of the factors supporting high production is the crop management system used by farmers. This research aims to analyse the level of adoption of Integrated Crop Management (ICM) in the paddy rice commodity in the Sesayap District. ICM is an innovative approach in agriculture aimed at reducing the use of chemical pesticides and promoting sustainable pest and disease control. This study was conducted to understand the extent to which farmers in Sesayap District have adopted ICM technology in paddy rice cultivation and the factors influencing this adoption. The research method was a structured questionnaire survey from a sample of paddy rice farmers in the Sesayap District. The sample was selected using the purposive sampling method, with the criteria that they are part of farmer groups and actively cultivate paddy rice. The total number of respondents obtained was 57 individuals. The primary data collected were then described to illustrate the level of ICM adoption and the influencing factors. The results of this research indicate that the level of ICM adoption in the paddy rice commodity in Sesayap District is at 105, categorising it as moderate. Significant factors influencing the adoption level include farmers' level of education, knowledge about ICM, accessibility to information sources and training on ICM, the availability of institutional support, and farmers' perception of the benefits and effectiveness of ICM in increasing productivity and reducing production costs.